The Origin and Evolution of Language and the Propagation of Organization - Robert K. Logan (tripleC: Communication, Capitalism & Critique)
In this presentation we will study propagating organization. We begin by examining the evolution and origin of language by briefly reviewing the impact of the phonetic alphabet (Logan 2004a), the evolution of notated language (Logan 2004b), the origin of language and culture (Logan 2006, 2007), the role of collaboration in knowledge management (Logan and Stokes 2004), the impact of “new media” (Logan in preparation). We will then connect this work to the propagating organization of all living organisms (Kauffman et al. in press) where we will show that information in biotic systems are the constraints that instruct living organisms how to operate. We will demonstrate that instructional or biotic information is quite different than the classical notion of information Shannon developed for addressing engineering problems in telecommunications. We also will show that biosemiosis is in some sense equivalent to propagating organization (Kauffman et al. in press). We then conclude our presentation with the speculation that there exist at least seven levels of biosemiosis.